2011
DOI: 10.1111/j.1759-5436.2011.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Crop Improvement in Sub-Saharan Africa: A Proposal for a Scalable and Inclusive Approach to Food Security

Abstract: In sub-Saharan Africa, modern varieties released by the formal seed sector cover only a small part of the total crop acreage. Participatory approaches to crop improvement and seed production have been developed to overcome some of the barriers to modern variety development and seed distribution, but have not been widely scaled up. Crowdsourcing, such as seen in online citizen science projects, might inspire new approaches to upscale farmer-participatory seed innovation, specifically aiming at household food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…Indeed, these fields may be considered as mother trials in which farmers identified the most desirable wheat genotypes. The top ranking varieties identified in this experiment, including several landraces topping MVs, are being redistributed and grown in fields autonomously managed by smallholder farmers with a crowd-sourcing approach 44 . By 2016, more than 900 individual households were reached in 24 villages.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, these fields may be considered as mother trials in which farmers identified the most desirable wheat genotypes. The top ranking varieties identified in this experiment, including several landraces topping MVs, are being redistributed and grown in fields autonomously managed by smallholder farmers with a crowd-sourcing approach 44 . By 2016, more than 900 individual households were reached in 24 villages.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we study the large-N citizen science approach proposed by Van Etten (2011) in an application to the detection of phenotypic differences between varieties of common bean, Phaseolus vulgaris L. (Sect. 2.1).…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of the initiative is: if farmers have the opportunity to access better information and different varieties, they are better able to choose what is appropriate for their conditions and cope with unpredictable weather [27, 28]. The Seeds for Needs initiative addresses the issue of access to information and seed variety by exposing farmers to more crop varieties and increasing their knowledge about different traits.…”
Section: Methodsmentioning
confidence: 99%